Muhammad PbUH Prophecy in Leadership: The Study of Principal Leadership on Teachers at One Indonesian Pesantren - KA Rahman; Ahmad Hariandi; Nanang Thohirin Musthofa (Ta'dib: Jurnal Pendidikan Islam, 2017)
This research focused on one Indonesian Pesantren located in the region of Muaro Jambi, Jambi. We used qualitative study with a case study approach aiming to gain an in-depth understanding and interpretation of the meaning, a thorough fact about the leadership of the principal in managing the teacher in the perspective of the prophecy of Prophet Muhammad PbUH in one Indonesian Pesantren. The research was undertaken as a qualitative research, a case study approach. The participants of the research consisted of four participants as shown in the table below. The findings show that the planning of teacher competency development program in the perspective of four prophecies of the prophet Muhammad PbUH in Pesantren has been carried out by the four participants. Planning begins with the participants' knowledge of the four characteristics of the Prophet’s prophecies in the Pesantren, based on the needs of individuals’ competencies of participants. In general, the planning has been going well because every activity was scheduled in such a way that does not interfere the student learning activities.